Hydrophobic physical solvents for pre-combustion CO2 capture: Experiments, computational simulations, and techno-economic analysis. (June 2016) - Siefert, N.S.; Agarwal, S.; Shi, F.; Shi, W.; Roth, E.A.; Hopkinson, D.; Kusuma, V.A.; Thompson, R.L.; Luebke, D.R.; Nulwala, H.B.
Graphical abstract: Abstract: We synthesized and measured the properties of two new, hydrophobic, physical solvents to capture CO2 from pre-combustion syngas streams at integrated gasification combined cycle (IGCC) power plants, and then estimated their levelized cost of capturing CO2 (LCOC). The first solvent is an amphiphilic solvent containing polar ethylene glycol segments and a non-polar siloxane portion (PEG-Siloxane-1). The second solvent is a hydrophobic ionic liquid: allyl-pyridinium bis(trifluoromethylsulfonyl)imide [aPy][Tf2 N]. The LCOC was estimated by importing physical properties of these solvents into AspenPlus, and then conducting a detailed, techno-economic analysis. Finally, the LCOC of these hydrophobic solvents was compared with the LCOC baseline solvent, Selexol. Our results suggest that PEG-Siloxane-1 is cost competitive with Selexol, and that [aPy][Tf2 N] could lower the cost of capturing CO2 compared with Selexol, depending on the cost to synthesize this ionic liquid at commercial scale.